2016
DOI: 10.1638/2015-0161.1
|View full text |Cite
|
Sign up to set email alerts
|

PLASMA BIOCHEMISTRY AND HEMATOLOGY REFERENCE VALUES OF CAPTIVE PANTHER CHAMELEONS (FURCIFER PARDALIS) WITH SPECIAL EMPHASIS ON SEASONALITY AND GENDER DIFFERENCES

Abstract: Blood samples of 86 captive panther chameleons (Furcifer pardalis) were collected in January and August from the ventral coccygeal vein in order to establish reference intervals of clinical healthy individuals under similar husbandry conditions for plasma biochemistry and hematology for this species. Significant differences were found in phosphorus, glucose, total protein, albumin, and white blood cell count between males and females in both seasons. Calcium, alanine aminotransferase, aspartate aminotransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In the present work, the erythrocyte count for A. adramitanus are 1526500, while for C. c. calyptratus is 1248333. These values are similar to those reported in Agama atra [4], Sitana ponticeriana [25], Laudakia caucasia and Laudakia stellio [31] and Furcifer pardalis [47].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present work, the erythrocyte count for A. adramitanus are 1526500, while for C. c. calyptratus is 1248333. These values are similar to those reported in Agama atra [4], Sitana ponticeriana [25], Laudakia caucasia and Laudakia stellio [31] and Furcifer pardalis [47].…”
Section: Discussionsupporting
confidence: 90%
“…Erythrocyte nuclei become condensed, stain darker as the cells age, and it is centrally located [21]. The shape of erythrocytes is oval or elongated or elliptical as in Lacerta rudis [17], some Scincid species [18], Agrionemys horsfieldi [21], Tupinambis merianae [27], Turkish snakes [28], sea turtles [30], Elaphe sauromates [34], four species from agamidae [32], Psammophilus Blanfordanus [33], three species of turtle from Iran [38], Naja naja [43], Neurergus kaiseri , Neurergus microspilotus [36], Emys orbicularis, Mauremys rivulata [45] and Furcifer pardalis [47], whereas the present study reported the oval or elliptical shape of erythrocyte and their nuclei in the examined species. Arikan & Çiçek [29] recorded interspecific and even intraspecific variations in terms of the lengths, widths and sizes of the erythrocytes and nuclei in 87 species belonging to amphibians and reptiles.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations in other reptile species indicated large differences between hematology values of different species as well as intraspecific variation as a function of season and sex [57,58]. In their study of blood chemistry and hematology in captive panther chameleons (Furcifer pardalis), Laube et al [59] found that lymphocytes were the predominant leukocyte type in both summer and winter. In contrast, Cuadrado et al [60] reported that heterophils were the most frequently found leucocyte type in dystoic and healthy post-reproductive females of the common chameleon (Chamaeleo chamaeleon).…”
Section: Baseline Stress Levels and Leukocyte Profilesmentioning
confidence: 99%
“…Furthermore, the interpretation of leukocyte dynamics relies on baseline data for the taxon of interest [66]. Reports about leukocyte profiles in chameleons in the wild [60,61] and captivity [59] are rare and based on relatively small sample sizes. Our study therefore contributes valuable comparative data based on large samples of two wild chameleon species, but future studies may want to assess stress levels more directly, e.g.…”
Section: Baseline Stress Levels and Leukocyte Profilesmentioning
confidence: 99%
“…Studies evaluating the health status and characteristics of free-ranging populations are, however, scarce or absent for most species, especially those that are rarely seen in the wild (Bell & Donnelly, 2006;Whitfield et al, 2007;Dallwig et al, 2011). In lizards, health assessments reported in the literature have usually been done on species that are threatened (Alberts et al, 1998;Espinosa-Avilés, Salomón-Soto & Morales-Martínez, 2008;McEntire et al, 2018), endemic (Lewbart et al, 2015;Arguedas et al, 2018), or kept in captivity (Ellman, 1997;Mayer et al, 2005;Laube et al, 2016), providing information on the survival of species with conservation issues. However, free-ranging species with no apparent threats have generally not been evaluated as well.…”
Section: Introductionmentioning
confidence: 99%